การพัฒนาแนวปฏิบัติทางคลินิกสำหรับการดูแลผู้สูงอายุที่เป็นโรคหลอดเลือดสมองในระยะฟื้นฟูสภาพ โรงพยาบาลเชียงใหม่ราม - พัชรียา พ่อค้า (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Stroke is a common disease in elderly people and can result in dependency. Therefore, development of clinical practice guidelines (CPGs) for elderly people with stroke in the rehabilitation phase is necessary for positive outcomes. This developmental study aimed to develop CPGs for elderly people with stroke needing rehabilitation care at Chiangmai Ram Hospital. The study based on the CPGs developmental-framework of the Australian National Health and Medication Research Council (NHMRC, 1999). The feasibility of the CPGs implementation was explored using a questionnaire with 17 people from a health care team. Data were analyzed using descriptive statistics. The results of the study were as follows: 1. The CPGs were developed from 42 evidences into 39 items. The guidelines consisted of five components: 1) assessment for rehabilitation care, 2) care of stroke rehabilitation, 3) education, 4) continuity of care, and 5) improved quality of care 2. After following the implementation of the CPGs, one hundred percent of the sample agreed that the CPGs implementation would enable all of the recommendations made. One hundred percent agreed that CPGs can solve problems or provide positive outcomes, and 94.12% agreed that the CPGs were appropriate and feasible for implementation in a ward unit. In addition, 88.24% of the sample agreed that the recommendations of the CPGs were clear and reduced cost, and 88.35% of the sample agreed that the CPGs were convenient to use, and providing ease of practice implementation. From the results of this study, it can be concluded that the CPGs were feasible for implementation. However, the CPGs can be adjusted and updated appropriately based on ongoing use and recommendations. These recommendations should be presented to the administration for further implementation and for quality of care.